The case of Antonio Stradivari 1718 ex-San Lorenzo violin: History, restorations and conservation perspectives. (February 2019) - Rovetta, T.; Invernizzi, C.; Fiocco, G.; Albano, M.; Licchelli, M.; Gulmini, M.; Alf, G.; Fabbri, D.; Rombolà, A.G.; Malagodi, M.
Abstract: Historic musical instruments, especially violins, have witnessed centuries of stories and events, passing from hand to hand among musicians, collectors and restorers. Historical last wills and trading documents makes it possible to reconstruct the movements around the world of the decorated ex-San Lorenzo violin and its story throughout its owners. The history of this precious violin began in 1718 in the Cremonese workshop of Antonio Stradivari. It represents a mature example of the Master's "Golden Age" period (1700 to 1720) and is unique for an unusual inscription "GLORIA ET DIVITIAE IN DOMO EIUS" which adorns its center-bout ribs. Numerous imaging techniques (stereomicroscopy, optical microscopy, VIS and UV photography, X-ray radiography, XRF mapping), spectroscopic (FORS, FTIR in reflectance mode, XRF, SEM-EDX) and chromatographic (Pyrolysis SolidPhase Microextraction Gas Chromatography-Mass spectrometry) were applied in order to: (i) give new data related to both original and restoration materials, (ii) make considerations about the restoration procedures adopted over the centuries, and (iii) highlight the main issues of historic musical instrument preservation. The material information gathered from this multi-technique study is varied depending on the areas under investigation. This analytical campaign, which is the widest ever made on a single musical instrument, gives a new overview of the materials applied on historic bowed musical instruments and opens debate about what should be preserved and how to do it. Highlights: Multi-analytical approach for in-depth knowledge of violin materials. A 'well-preserved' violin hides centuries old retouching and modifications. Different protective layers mean different approaches to preservation.